PENGARUH BRAIN GYM TERHADAP PENINGKATAN KOORDINASI GERAK EKUILIRIBIUM PADA ANAK 7-8 TAHUN DI SD MUHAMMADIYAH 4 DEPOK - Nurbaiti Kholishoh (2022)
Background : Healthy children must have good growth and development. Children aged 7-8 years have coordination of movements that are not optimal. Age 7-8 years is the initial phase of increasing dynamic balance abilities in girls and boys. Cognitive development can be achieved by various stimuli both by parents and teachers. Children's development can be through brain exercise. Brain exercise that can stimulate cognitive development through brain switches, thereby activating positive energy in school children. In this study, a measuring instrument for checking the coordination of equilibrium was used. The purpose of this study was to determine the effect of Brain Gym on Equilibrium Movement Coordination in children 7-8 years old at SD Muhammadiyah 04 Depok. The research method used pre-experimental research design with pre-test and post-test. The number of samples used in this study were 2nd grade students of SD Muhammadiyah 04 Depok aged 7-8 years with a total of 60 samples. The results of data analysis using the Kolmogrov Smirnov test. The results of the Paired Sample T-test showed that there was an effect of Brain Gym on the improvement of equilibrium movement coordination in children 7-8 years with a significant value of 0.000 (P < 0.05). There is an effect of Brain Gym on the improvement of equilibrium movement coordination in children 7-8 years old.